PERBEDAAN PENGARUH SENAM ZUMBA DAN SENAM AEROBIK TERHADAP PENURUNAN BERAT BADAN PADA WANITA DEWASA OBESITAS I - Delfi Ramadhini; Sri Sartika Sari Dewi (Jurnal Kesehatan Medika Saintika, 2020)
The number of obese sufferers in Padangsidimpuan City is 661 out of 4,800 who are overweight and 527 out of 661 obese people are women. One of the management of obesity is increasing physical activity through exercise. Gymnastics has long been used to help burn fat. The purpose of this study was to identify the differences in the effects of aerobic exercise and zumba exercise on weight loss in adult women with obesity I. This study used a quasy-experimental design with pre and post test two group designs. The number of samples in the study were 19 people in Group I (zumba) and 19 people in group II (aerobics). Data were analyzed by normality test using the Shapiro-Wilk test, hypothesis testing I and II using paired sample t-test and hypothesis testing III using the independent sample t-test. Hypothesis I test the value of ρ = 0.001 (ρ <0.05), there is an effect of Zumba exercise on weight loss. Hypothesis II, the value of ρ = 0.001 (ρ <0.05), there is an effect of aerobic exercise on weight loss. Hypothesis testing III, the value of ρ = 0.375 (ρ> 0.05), there is no difference in the effect of zumba and aerobics on weight loss. The conclusion of the study is that there is an effect of zumba and aerobics on weight loss, but there is no difference in the effect of zumba and aerobics on weight loss in obese I adult women.